The nomos of decision within myths and rebellion:: Prometheus, the persians and Antigone - GRASSO, VITTORIA (Revista DIAPHONÍA, 2025)
The paper analyses how political decision-making against tyranny is manifested in ancient Greece through nomos. In this dimension, the concepts of themis, dike and nomos as the balance between force and justice are considered. The decision is configured in the parameters of decision and rebellion in the tragedies and myths, such as that of Prometheus and Antigone who embody disobedience in the face of arbitrary laws and the Persians by Aeschylus, where in front of the enemy the population consider themselves as "no man’s servants," who can govern themselves by just reacting to the established decision-making process. It investigates, then, how political technique and the ability to make decisions are, to a certain extent, reflective of each other and fundamental to civil liberty and the struggle against oppression.